Transitivity and Subject Positions in Old Irish. - Lash, Elliott (Transactions of the Philological Society, 2020)
This article is concerned with some fine‐grained distinctions in the syntax of subjects in Old Irish. Old Irish (7th–9th century) is typically described as a VSO language, but there are a number of sentences in the corpus in which the subject is not immediately after the subject. In this paper two case studies are conducted the results of which show that (a) non‐final late subjects are confined to non‐transitive and 'atypical transitive' clauses having the general form VXSY, and (b) the position of final late subjects in the schema VXS# can understood in descriptive terms as 'right‐dislocated' and motivated largely in information structure terms (i.e. Topic‐Comment, Focus‐Alternative), although a small residue of examples are similar to the VXSY‐type of case in being 'atypical transitives'. The descriptive term 'atypical transitive' is introduced here to cover morphologically transitive clauses (with accusative marked direct objects nouns, or pronouns that can replace such nouns) that behave syntactically more like non‐transitive clauses. There are four types: negative clauses with bare indefinite objects, clauses with object‐oriented floating quantifiers, clauses in which a pronominal object serves to 'detransitivize' the verb, and clauses containing a verb of motion whose direct object is the goal of movement.